(3GdTGed aj aQhY GdTGaYjIs - (3YHO GdSjO Hf eMeO Hf YHO GdhGMO, CHh fUQ, GHf GdUHGZ,J (B477 (3g` s
(3ChdgG (B:s
(3Chdg aUd (B: (3aCeG ef NU GdeCchd aJYdb Hbhd GdfHj Udi Gddg Ydjg hSde OHGZ GdCOje PcGJg s
(3BNQgG (B:s
(3jfJgj HaUd (B: (3EPG COQc GdeCehe GdEeGe ai GdbQGAI hONd ehdgG SbWJ s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B10 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B232s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1025s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3Gdabg GdTGaYjs